Yield and Quality of Pacific white shrimp Litopenaeus vannamei (Boone, 1931) in response to different Killing Methods - Bhat, T. H.; Aman Hassan, Md.; Chouksey, M. K.; Balange, A. K.; Nayak, B. B. (Fishery Technology, 2018)
The present study compares the differences in theeffect of two methods of slaughtering i.e. by coldshock in ice water slurry (hypothermia) and bytaking out of water (asphyxia) on the quality ofwhite shrimp (Litopenaeus vannamei). Yield, proximatecomposition, pH, calcium ATPase activity,texture and colour parameters were compared. Nosignificant differences were found in the yield,proximate composition, pH and calcium ATPaseactivity between the shrimp killed by the twodifferent methods. Texture and colour were foundto vary significantly (p